Oral Metastasis to the Oral Cavity - An Emerging Prostate Cancer Risk Factor: A Review - Varun Rastogi; Nisha Maddheshiya (Journal of Universal College of Medical Sciences, 2024)
ABSTRACT Metastatic tumors involving the jaw constitute a rare occurrence, encompassing approximately 1% to 4% of all oral malignancies resulting from distant primary tumors. Among the leading sources of metastatic tumors to the oral or maxillofacial region are breast, lung, prostate, kidney, bone, colon, rectum, thyroid, stomach, testis, bladder, ovary, and cervix cancers. Oral cavity metastatic tumors are infrequent, comprising approximately 1% of all oral malignancies. Remarkably, in 25% of cases, the presence of oral metastasis serves as the initial indicator of metastatic progression, while in 23%, it constitutes the earliest discernible evidence of malignancy spreading from its primary origin. Prostate cancer typically originates from the basal cells within the prostate, and it ranks as the 6th most common cause of cancer-related mortality among males worldwide. Prostate cancer is indeed a signiﬁcant health concern for men, its prevalence and impact on male health underscore the importance of regular screening, early detection, and appropriate medical management to improve outcomes and reduce mortality rates. In our review, we explore different risk factors and predisposing conditions, as well as the primary pathway through which prostate carcinoma metastasizes to the oral cavity.